Study of electrical, chemical and structural characteristics of superconductor thin film obtained by polymeric precursors method - Carvalho, C. L.; Peruzzi, R. O.; Junior, D. R. (Materials Research Society, 2005)
Superconductor films of the BSCCO system have been grown by dip coating technique with good success. The chemical method allows us to grow high temperature superconductor thin films to get better control of stoichiometry, large areas and is cheaper than other methods. There is a great technological interest in growth oriented superconductor films due anisotropic characteristics of superconductor materials of high critical temperature, specifically the cuprates, as we know that the orientation may increase the electrical transport properties. Based on this, the polymeric precursor method has been used to obtain thin films of the BSCCO system. In this work we have applied that method together with the deposition technique known as dip coating to obtain Bi-based superconductor thin films, specifically, Bi1.6Pb0.4Sr2.0C2.0Cu3.0Ox+8, also known as 2223 phase with a critical temperature around 110 K. The films with multilayers have been grown on crystalline substrates of LaAlO3 and orientated (100) after being heat treated around 790 degrees C - 820 degrees C in lapse time of 1 hour in a controlled atmosphere. XRD measurements have shown the presence of a crystalline phase 2212 with a critical temperature around 85 K with (001) orientation, as well as a small fraction of 2223 phase. SEM has shown a low uniformity and some cracks that maybe related to the applied heat treatment. WDS has also been used to study the films composition. Different heat treatments have been used with the aim to increase the percentage of 2223 phase. Measurements of resistivity confirmed the presence of at least two crystalline phases, 2212 and 2223, with T-c around 85 K and 110 K, respectively.